THE EFFECTIVENESS OF IMAGE-GUIDED INTERVENTIONS IN PAIN MANAGEMENT AND MINIMALLY INVASIVE PROCEDURES - Hassel Mohammed Hasil Alasmary, Mousa Mohammed Abdullah Matabi, Turki Abdullah Turki Alkhathlan, Mohammed Abdullah Fahad Alshahrani, Mosa Mohammed I Alassiri, Abdulziz Hamad Almannaa, ‏Ahmed Mohsen Attafi, ,; Salem Abduallah Almarshid, Faisal Abdulaziz Almutairi, Ahmed Ali Hmoud Mashykhei, Meshal Zayed Alotaibi, Qutaiba Saad Alabdulatif, ,; Abdullah Turki Al-Otaibi, Ahmed Mohammed Huraysi, Afnan Ahmed Shbeli, Khalid Ayed Ali Alshahrani, (Chelonian Research Foundation, 2022)
Photoacoustic imaging is a developing technique that may be used for image-guided interventional treatments. This imaging technique has a distinctive capability to provide immediate, non-intrusive, economical, and radiation-free assistance in a practical surgical setting. This article provides evidence and highlights promising outcomes of studies using photoacoustic imaging to guide medication distribution, treatment, surgery, and biopsy. Therefore, this minireview will aid in advancing future research and practical implementation of photoacoustic image-guided therapies (1,2). Photoacoustic imaging (PAI), also known as optoacoustic imaging, is a new therapeutic imaging technique that combines the advantages of optical and ultrasonic imaging. In PAI, a target produces photoacoustic waves when it is exposed to brief laser pulses. The generated photoacoustic (PA) waves will be subsequently captured by an ultrasound transducer to create images. The contrast in photoacoustic imaging (PAI) is determined by the optical absorption and is not affected by the mechanical properties or elasticity. The spatial resolution of PAI can be adjusted to penetrate up to 5 cm, which is significantly deeper than traditional optical imaging methods in soft tissue . (3,4) Photoacoustic imaging (PAI) has significant promise for clinical diagnosis of a wide range of disorders, including cancer, stroke, atherosclerosis, arthritis, and more. PAI has several applications in the field of cancer, such as early detection, determining the stages and metastases, treatment planning, and assessment. Studies have shown that PAI is effective in diagnosing breast, prostate, thyroid, melanoma, and ovarian cancers (5-8). PAI, or Photoacoustic Imaging, is used in stroke cases to visualize and analyze mechanical thrombolysis, vessel segmentation, and other vessel injuries in the brain (9,10). It is also helpful in assessing plaque distinction and characterization, as well as detecting macrophages and lipids in atherosclerosis plaques. PAI has also been used in the field of arthritis to identify inflammation stage the disease, and assess its severity.(11-14)